1988
DOI: 10.1164/ajrccm/137.1.149
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Infection with Nontuberculous Mycobacteria

Abstract: Nontuberculous mycobacterial infections (NTM) are being increasingly recognized as a cause of chronic pulmonary disease. We recently reviewed the clinical, radiologic, and bacteriologic presentation of 89 adult patients ill enough to have been hospitalized between 1981 and 1985 with the diagnosis of NTM. Preexisting lung disease was present in 82% and alcohol abuse in 40%. Although M. avium complex was identified in 51% of the patients, M. xenopi, which is usually reported to occur infrequently, accounted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
2
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(75 citation statements)
references
References 13 publications
2
70
2
1
Order By: Relevance
“…Preexisting lung disease was present in 35 cases (74%), of which healed TBC disease accounted for 14, chronic bronchitis and emphysema for 12, and bronchiectasis for three; whereas three other patients had interstitial pulmonary fibrosis. In the Canadian province ofOntario, M. xenopiis a relatively common NTM isolate, and numerous cases of disease due to this species have been observed [42,78,79). Until now, reports of M. xenopicases from the United States have remained rather rare [52].…”
Section: Site Of Mycobacteriosismentioning
confidence: 99%
“…Preexisting lung disease was present in 35 cases (74%), of which healed TBC disease accounted for 14, chronic bronchitis and emphysema for 12, and bronchiectasis for three; whereas three other patients had interstitial pulmonary fibrosis. In the Canadian province ofOntario, M. xenopiis a relatively common NTM isolate, and numerous cases of disease due to this species have been observed [42,78,79). Until now, reports of M. xenopicases from the United States have remained rather rare [52].…”
Section: Site Of Mycobacteriosismentioning
confidence: 99%
“…Preexisting pulmonary diseases include pneumoconiosis (256), chronic obstructive pulmonary disease (179), and impaired ventilatory function (6). In a 1988 review of nontuberculous pulmonary infections in patients admitted to a Toronto hospital, 8 (9%) of 89 patients had infections that were caused by M. kansasii, and of those 8 patients, 5 had underlying lung disease, 3 had chronic liver disease, 2 smoked, and 2 reported alcohol abuse (91). No common risk factors could be identified among the remaining patients.…”
Section: Risk Factors For M Kansasii Infectionmentioning
confidence: 99%
“…Those conditions include pneumoconiosis and silicosis, due to chronic and long-term exposure to dusts as a result of occupations (e.g., coal mining and farming) (445,547). In one study of 45 patients with M. avium complex pulmonary disease, 33 (73%) patients had preexisting pulmonary disease, 17 smoked (38%), and 15 (33%) reported alcohol abuse (91). The prognosis in M. avium complex pulmonary infections was strongly influenced by the associated disease (425).…”
Section: Epidemiology Of M Avium Complex Infectionmentioning
confidence: 99%
“…The prognosis in M. avium complex pulmonary infections was strongly correlated with the underlying condition (44). Older studies of treatment and the natural history of disease showed that patients who are symptomatic have progressive disease that is difficult to treat, whereas many of those who were asymptomatic at the time of isolation went on to develop invasive disease (20).…”
Section: Mycobacterium Avium-intracellulare Pulmonary Diseasementioning
confidence: 99%